Heimatbuchok Köztes-Európa emlékezetirodalmában = Heimatbuch in the literary memory of Central Europe - Takács, Katalin (Közép-Európai Közlemények, 2018)
Although numerous works – of varying quality and literary value – have been published about post-WWII German collective guilt in relation to the Germans’ expulsion from their ancestral homelands and the bitter experiences associated with it, the systematic review of these works has escaped the consideration of researchers to this day. In our presentation, having taken a look at the memoirs and chronicles of the generation of Germans expelled from Hungary (the so-called Erlebnisgeneration), we investigate an issue that involved several other Central European states. Methodologically using Jan Assmann’s concept of cultural memory, while bearing in mind Maurice Halbwach’s and Pierre Nora’s earlier related work, we attempt to place Heimatbuch within the framework of literary memory. We show how memory is capable of constructing a place of recollection from a hometown such that everything associated with it may be recalled and available via collective memory. In the life of a people or ethnic group, these places, having been elevated to bearers of remembrance, serve not only as stages of interaction, but as symbols of our identity and as markers for our memory.